2012
DOI: 10.1016/j.jconrel.2012.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Microneedle delivery of plasmid DNA to living human skin: Formulation coating, skin insertion and gene expression

Abstract: Microneedle delivery of nucleic acids, in particular plasmid DNA (pDNA), to the skin represents a potential new approach for the clinical management of genetic skin diseases and cutaneous cancers, and for intracutaneous genetic immunization. In this study excised human skin explants were used to investigate and optimize key parameters that will determine stable and effective microneedle-facilitated pDNA delivery. These include (i) high dose-loading of pDNA onto microneedle surfaces, (ii) stability and function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 37 publications
(50 reference statements)
1
90
0
Order By: Relevance
“…Given that PVP has previously been reported to form hydrogen bonds with DNA, this loss in transfection efficacy was not entirely unexpected. 26 This then prompted us in this study to examine the suitability of 4 FDA-approved polymer formulations to form dissolvable microneedles for DNA vaccination. In addition, we incorporated the amphipathic cationic peptide RALA prior to formulation to enhance the functionality of the DNA cargo.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that PVP has previously been reported to form hydrogen bonds with DNA, this loss in transfection efficacy was not entirely unexpected. 26 This then prompted us in this study to examine the suitability of 4 FDA-approved polymer formulations to form dissolvable microneedles for DNA vaccination. In addition, we incorporated the amphipathic cationic peptide RALA prior to formulation to enhance the functionality of the DNA cargo.…”
Section: Discussionmentioning
confidence: 99%
“…1), which is similar to or greater than the penetration depths achieved using solid or coated needles. 26,30,43 Therefore we could be confident that a large proportion of the payload within the dissolvable polymer matrix would be deposited into the skin following microneedle insertion. The microneedle type can affect the outcomes of incomplete insertion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further in vivo studies with these formulations will research the ability of these systems controlled-release pDNA expression. But the results showed that the total number of positive expression was less than solution prescription in 24 h. However, due to the design, the drug can only be loaded onto the surface of MNs, so the drug loading amount is relatively low [23][24][25]. The cost of fabrication is also another concern.…”
Section: Problems Of Non-hydrogel Mnsmentioning
confidence: 99%